Growth of Lettuce (Lactuca sativa L.) Plant in Light Organic Fertilizer Media From Goat and Rabbit Dirty - Kusuma Wardany; Sulis Anjarwati (IJECA (International Journal of Education and Curriculum Application), 2020)
Goat droppings and rabbit droppings are types of animal droppings that have not been maximally utilized. If treated with both types of impurities can produce liquid organic fertilizer that can be used in agriculture. The purpose of this study was to determine the effect of liquid organic fertilizer from goat manure and rabbit manure on the growth of lettuce (Lactuca sativa L.). This research was carried out in the agricultural land in the rice field area of Purbolinggo District, East Lampung.The method used in this study was an experiment using a completely randomized design (CRD) pattern of one factor, namely the type of liquid organic fertilizer from goat manure and rabbit feces three times. The data obtained were analyzed by quantitative descriptive analysis. The best treatment for stem height growth is P1 (liquid fertilizer of 500 ml goat manure), with an average growth of 1.8 cm for one month. The best treatment for the number of leaves is P2 (500 ml rabbit manure liquid fertilizer), with an average growth of 4 leave.